2021
DOI: 10.1111/tpj.15483
|View full text |Cite
|
Sign up to set email alerts
|

Developing climate‐resilient crops: improving plant tolerance to stress combination

Abstract: Global warming and climate change are driving an alarming increase in the frequency and intensity of different abiotic stresses, such as droughts, heat waves, cold snaps, and flooding, negatively affecting crop yields and causing food shortages. Climate change is also altering the composition and behavior of different insect and pathogen populations adding to yield losses worldwide. Additional constraints to agriculture are caused by the increasing amounts of human-generated pollutants, as well as the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
206
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(260 citation statements)
references
References 203 publications
0
206
0
Order By: Relevance
“…Since plants are often exposed to stress combinations in nature and our understanding of how plants respond to these combinations is lacking 29,62 , we have exposed Marchantia to 19 possible combinations of the seven abiotic stresses (darkness+high light and cold+heat being mutually exclusive). Interestingly, purely physical stresses (cold, heat, darkness, and high light) showed a higher number of DEGs than chemical stresses (salt, mannitol, and nitrogen deficiency) (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since plants are often exposed to stress combinations in nature and our understanding of how plants respond to these combinations is lacking 29,62 , we have exposed Marchantia to 19 possible combinations of the seven abiotic stresses (darkness+high light and cold+heat being mutually exclusive). Interestingly, purely physical stresses (cold, heat, darkness, and high light) showed a higher number of DEGs than chemical stresses (salt, mannitol, and nitrogen deficiency) (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…For example, drought causes plants to close their stomata to minimize water loss 25,26 , while heat causes the stomata to open to cool down their leaves via transpiration 21,27,28 . The stress signalling is mediated by a diverse ensemble of stress-specific sensors/receptors, networks of protein kinases/phosphatases, calcium channels/pumps, and transcription factors that can be localized to different organelles 29,30 . Stress signalling is further communicated and attenuated by hormones, other signalling molecules (e.g., reactive oxygen species) and protein modifications (s-nitrosylation, ubiquitination, myristoylation) 31,32 .…”
mentioning
confidence: 99%
“…A closer inspection of the database search revealed that only about 1% of the original articles had stress combination as a subject [49]. However, this could be changed due to extensive research on climate change and its multifactorial nature affecting unpredictable combinations of different stresses and posing an even greater threat to major crops [50]. Mittler [51] proposed a stress matrix approach to visualize the individual positive and/or negative interactions among different stresses and their overall effect on plant growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Plant reproduction, i.e., the developmental process of flower organs (including stamens and stigma), the maturation of pollen and egg cells, pollen shedding, interactions with stigma, germination, growth and eventually fertilization, as well as embryo development and seed filling, are all highly sensitive to elevated temperatures (Santiago and Sharkey, 2019;Djanaguiraman et al, 2020;Chaturvedi et al, 2021;Sze et al, 2021). It was recently proposed that the tightly synchronized nature of the developmental programs involved in these processes, as well as their reliance on certain stress-related programs (e.g., the stress-associated desiccation program of pollen grains), reactive oxygen species (ROS) and hormone signaling, under non-stress conditions, makes them more sensitive to stress (Sinha et al, 2021;Sze et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The unyielding increase in atmospheric and oceanic temperatures, termed ‘global warming’, is causing drastic changes in our climate, termed ‘climate change’ (Lobell et al, 2011; Steg, 2018; Bailey-Serres et al, 2019; Alizadeh et al, 2020; Overpeck and Udall, 2020; von der Gathen et al, 2021; Zandalinas et al, 2021; Zhai et al, 2021). As a result, large areas of our planet are increasingly exposed to floods or extended droughts combined with extreme temperatures (Mazdiyasni and AghaKouchak, 2015; Alizadeh et al, 2020; Overpeck and Udall, 2020; Rivero et al, 2021; Zandalinas et al, 2021). Historically, extended droughts combined with heat waves have been the cause of catastrophic reductions in agricultural productivity estimated at billions of dollars per episode ( e.g., the drought and heat wave combination events occurring during the summers of 1980 and 1988 in the US resulted in losses to agriculture estimated at 33 and 44 billion dollars, respectively; https://www.ncdc.noaa.gov/billions/ ; Mittler, 2006; Lobell et al, 2011; Rivero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%